International network for comparison of HIV neutralization assays: the NeutNet report. - Eva Maria Fenyö; Alan Heath; Stefania Dispinseri; Harvey Holmes; Paolo Lusso; Susan Zolla-Pazner; Helen Donners; Leo Heyndrickx; Jose Alcami; Vera Bongertz; Christian Jassoy; Mauro Malnati; et al. (PLoS ONE)
Background Neutralizing antibody assessments play a central role in human immunodeficiency virus type-1 (HIV-1) vaccine development but it is unclear which assay, or combination of assays, will provide reliable measures of correlates of protection. To address this, an international collaboration (NeutNet) involving 18 independent participants was organized to compare different assays. Methods Each laboratory evaluated four neutralizing reagents (TriMab, 447-52D, 4E10, sCD4) at a given range of concentrations against a panel of 11 viruses representing a wide range of genetic subtypes and phenotypes. A total of 16 different assays were compared. The assays utilized either uncloned virus produced in peripheral blood mononuclear cells (PBMCs) (virus infectivity assays, VI assays), or their Env-pseudotyped (gp160) derivatives produced in 293T cells (PSV assays) from molecular clones or uncloned virus. Target cells included PBMC and genetically-engineered cell lines in either a single- or multiple-cycle infection format. Infection was quantified by using a range of assay read-outs that included extracellular or intracellular p24 antigen detection, RNA quantification and luciferase and beta-galactosidase reporter gene expression. Findings PSV assays were generally more sensitive than VI assays, but there were important differences according to the virus and inhibitor used. For example, for TriMab, the mean IC50 was always lower in PSV than in VI assays. However, with 4E10 or sCD4 some viruses were neutralized with a lower IC50 in VI assays than in the PSV assays. Inter-laboratory concordance was slightly better for PSV than for VI assays with some viruses, but for other viruses agreement between laboratories was limited and depended on both the virus and the neutralizing reagent. Conclusions The NeutNet project demonstrated clear differences in assay sensitivity that were dependent on both the neutralizing reagent and the virus. No single assay was capable of detecting the entire spectrum of neutralizing activities. Since it is not known which in vitro assay correlates with in vivo protection, a range of neutralization assays is recommended for vaccine evaluation.